User willingness to pay for natural resource conservation at Bach Long Vy Island, Vietnam - Hoang Thi, Chien; Kirby, Mitchell; Dinh Tran, Lan (Vietnam Journal of Earth Sciences, 2022)
Tourism development plays a crucial role in creating employment, boosting the revenue of the economy, supporting to improve the living standard. While tourism provides many opportunities to improve the well-being of local communities, the expansion of tourism needs to be effectively managed to avoid the degradation of natural capital. Assessing resource awareness and use behavior is an effective way to determine the public’s commitment to natural resource conservation and restoration in protected areas. The research was performed in Bach Long Vy Island (BLVI) in Hai Phong city, Viet Nam which is the first National Marine protected area designated by the Vietnamese Government. The aim of this study was to estimate tourists’ Willingness to pay (WTP) for natural resource conservation at BLVI through using Contingent valuation method (CVM) with the single-bounded dichotomous choice technique and the random utility model. We estimate the average visitor WTP is VND 153 370 per year (approx. US$6.58), while the aggregate WTP of tourists for the environmental conservation is VND 7.67 million per year (approx. US$32 900) (currency conversions taken as the average rate in September 2020; US$1 to VND 23280). The calculated results show that income and gender factors have significant effects visitors WTP whereas age and education have opposite effects. The outcomes of this research demonstrate the potential tourism value of this island due to the natural amenities and high biodiversity, particularly originating from its marine ecosystems. This result provides valuable scientific information for decision makers and local authorities and should be useful in establishing strategies to prevent the deterioration of ecosystems at BLVI (e.g., an environmental charge or entrance fee), thus contributing to sustainable tourism development.